Role of the microbiome in pathophysiology of necrotising enterocolitis in preterm neonates - Ondrej Slaby; Andrea Stanikova; Martin Jouza; Julia Bohosova; Petr Jabandziev (BMJ Publishing Group, 2023)
Although necrotising enterocolitis (NEC) is a serious, life-threatening disease, improved neonatal care is increasing the number of survivors with NEC among extremely preterm neonates. Therapy is nevertheless mostly symptomatic and the mortality rate remains high, especially among neonates requiring surgery. Therefore, it is important to focus on preventing the disease and modifiable risk factors. NEC's pathophysiology is multifaceted, with key factors being immaturity of the immune and barrier protective mechanisms of the premature gut and exaggerated proinflammatory reaction to insults like gut hypoxia, enteral nutrition or microbial dysbiosis. The role of the intestinal microbiome in the pathophysiology of NEC has been a subject of research for many years, but to date no specific pathogen or type of dysbiosis has been connected with NEC development. This review assesses current knowledge as to the role of the intestinal microbiota in the pathophysiology of NEC and the possibilities for positively influencing it